Digital Transformation in Public Administration: Strategies for Improving the Quality of E-Government-Based Public Services - Sina, Mario Loe (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze digital transformation strategies in public administration as an effort to improve the quality of e-government-based public services. The study used a qualitative approach with a case study design supported by a literature review. Data were obtained through in-depth interviews, observations, and documentation at government agencies that have implemented digital-based services. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion using triangulation techniques to ensure data validity. The results show that digital transformation has a positive impact on improving the quality of public services, particularly in aspects of reliability, responsiveness, transparency, and ease of access to services. The implementation of e-government systems can accelerate administrative processes, reduce complicated bureaucratic procedures, and increase service accountability. However, challenges faced include limited technological infrastructure, the digital literacy gap among the public, and resistance from some officials to change. The success of digital transformation is greatly influenced by visionary leadership, adaptive regulatory support, and increased human resource competency. Therefore, digital transformation strategies must be implemented in an integrated and sustainable manner to achieve public services that are effective, inclusive, and responsive to community needs.